Does quality of life improve in octogenarians following cardiac surgery? A systematic review. Issue 4 (28th April 2015) - Abah, Udo; Dunne, Mike; Cook, Andrew; Hoole, Stephen; Brayne, Carol; Vale, Luke; Large, Stephen
Abstract : Objectives: Current outcome measures in cardiac surgery are largely described in terms of mortality. Given the changing demographic profiles and increasingly aged populations referred for cardiac surgery this may not be the most appropriate measure. Postoperative quality of life is an outcome of importance to all ages, but perhaps particularly so for those whose absolute life expectancy is limited by virtue of age. We undertook a systematic review of the literature to clarify and summarise the existing evidence regarding postoperative quality of life of older people following cardiac surgery. For the purpose of this review we defined our population as people aged 80 years of age or over. Methods: A systematic review of MEDLINE, EMBASE, Cochrane Library, trial registers and conference abstracts was undertaken to identify studies addressing quality of life following cardiac surgery in patients 80 or over. Results: Forty-four studies were identified that addressed this topic, of these nine were prospective therefore overall conclusions are drawn from largely retrospective observational studies. No randomised controlled data were identified. Conclusions: Overall there appears to be an improvement in quality of life in the majority of elderly patients following cardiac surgery, however there was a minority in whom quality of life declined (8–19%). There is an urgent need to validate these data and if correct to develop a robust prediction tool to identify these patients before surgery. Such a tool could guide informed consent, policy development and resource allocation.